Factor Analysis of The Incidence of Stunting in Children Under Five - Siska Damayanti; Dianita Ekawati; Lilis Suryani; Chairil Zaman (School of Health Sciences Al-Ma'arif, 2025)
Stunting in children under five can result in impaired growth and development of children due to chronic malnutrition and repeated infections, which are characterized by below-standard length or height. The purpose of this study was to determine the factors associated with the incidence of stunting in the working area of the Sandar Angin Health Center in Pagar Alam City in 2024. This research method with a quantitative approach uses a cross-sectional design. The sampling technique is simple purposive sampling. The population of this study were all children under five who visited the Sandar Angin Health Center in Pagar Alam City in January 2024, Respondents totaled 94 respondents. Research Results The results of the Chi Square test obtained complementary feeding p value 0.004, gender p value 0.636, occupation Chi Square p value 0.021, comorbidities p value 0.42. smoking habits p value 0.000, nutritional status p value 0.000. Conclusion There is a significant relationship between MPAS, occupation, smoking habits and nutritional status with the incidence of stunting, while there is no relationship between gender, and comorbidities with the incidence of stunting. It is hoped that the Sandar Angin Health Center in Pagar Alam City will improve the health service sector.